Four new species of Phoenicagrion von Ellenrieder, 2008 from Brazil (Odonata, Coenagrionidae) - Machado, Angelo B. M. (Zootaxa, 2010)
Four new species of Phoenicagrion von Ellenrieder, 2008, P.flavescens, P. ibseni, P. karaja, and P. megalobos are described and illustrated. A key is provided for the six species of the genus.